InGaN doping for high carrier concentration in plasma‐assisted molecular beam epitaxy. Issue 3 (28th January 2014) - Gherasoiu, Iulian; Yu, Kin Man; Reichertz, Lothar A.; Walukiewicz, Wladek
Abstract: Magnesium is the only known effective p‐type dopant for nitride semiconductors. Although the p‐doping is challenging for AlN and GaN, requiring the activation of the Mg acceptors, in the case of the MOCVD growth, methods for obtaining reliable and high level doping have been developed. Similarly for n‐type doping silicon has been used successfully for more than a decade. More recently germanium has been found to be as effective for n‐type doping, with the additional advantage of inducing less strain in the host lattice due its size similarity to gallium. Doping of InGaN is more challenging due the difficulty in controlling the donor background associated with material extended defects and the incorporation of impurities. Although successful p‐type doping of InGaN with Mg has been demonstrated, quantitative limits for the magnesium incorporation and its behavior have not been analyzed. In this paper we investigate both, Mg and Ge doping of InGaN. We also discuss the challenges posed by the growth and measurement of the InGaN pn‐junctions characteristics as well as we demonstrate the fabrication of large area long wavelength LEDs on silicon (111) by PA‐MBE. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)